Promoting Anti-Fraud Culture in Indonesian Labor Migration for Economic Growth - Kusumawati, Mustika Prabaningrum (Jurnal Cakrawala Hukum, 2025)
This research examines the related the Constitution ensures that every citizen has the right to obtain decent employment and livelihood. This provision signifies the state’s responsibility to provide opportunities for citizens to work both domestically and abroad as Indonesian Migrant Workers (PMI). Limited job opportunities are seen as a major reason why many Indonesians prefer working overseas as PMI rather than facing unemployment at home. The continuous growth in the number of PMI, along with rapid technological advancements each year, has led to a greater risk of fraud, particularly the emergence of fake remittance agents across interconnected countries. To foster an anti-fraud culture in the deployment of PMI and to enhance trust and convenience in financial transactions, it is essential to develop an integrated, technology-based ecosystem. At least eight supporting elements are needed to establish this system: government institutions, banking sectors, fintech companies, educational institutions, marketing models, officially registered PMI placement agencies, procedural management for PMI, and PMI-related data analysis. The remittances sent by PMI are expected to contribute significantly to Indonesia’s economic growth.